2021
DOI: 10.1016/j.cej.2021.129039
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in estimating SARS-CoV-2 prevalence by wastewater-based epidemiology

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
139
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(174 citation statements)
references
References 116 publications
(115 reference statements)
1
139
0
1
Order By: Relevance
“…In addition to the secondary treatment evaluation, our study provided insights on the role of primary treatment only in the removal of SARS-CoV-2 RNA, as well as the addition of a tertiary process in the water line. The obtained results on the primary treatment SARS-CoV-2 RNA removal of 0.48 ± 1.17 log are in the range of previously reported elimination for WWTPs primary treatment (Abu A li et al 2021 ) that observed an elimination close to 1 log. Whereas no detection of SARS-CoV-2 RNA was determined after the addition of chlorination, applied as tertiary treatment.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…In addition to the secondary treatment evaluation, our study provided insights on the role of primary treatment only in the removal of SARS-CoV-2 RNA, as well as the addition of a tertiary process in the water line. The obtained results on the primary treatment SARS-CoV-2 RNA removal of 0.48 ± 1.17 log are in the range of previously reported elimination for WWTPs primary treatment (Abu A li et al 2021 ) that observed an elimination close to 1 log. Whereas no detection of SARS-CoV-2 RNA was determined after the addition of chlorination, applied as tertiary treatment.…”
Section: Resultssupporting
confidence: 79%
“…Besides, some factors could provoke variability in the reported SARS-CoV-2 RNA concentration in wastewater. For instance, in a thorough assessment of uncertainty in SARS-CoV-2 prevalence estimation by wastewater-based epidemiology, Li et al (2021) pinpointed precipitation and the decay in sewers as major obstacles to prevent higher accuracy. Correlation between higher COVID-19 incidence and positive samples in wastewater has been observed in previous studies, although high variability in detection has already been reported.…”
Section: Resultsmentioning
confidence: 99%
“…An accurate estimation of case number will help us finetune the viral load model, and the calibrated model may be used to perform back-calculation of actual cases based on wastewater viral load. However, this is another huge challenge in the application of WBE and is currently subject to significant uncertainties [52], more thorough studies are needed to take the model to the next stage. Improving the assay sensitivity has also been proposed as a solution.…”
Section: Resultsmentioning
confidence: 99%
“…Possible recommendations may be towards lockdown or quarantine. Researchers in Australia, the Netherlands, Sweden, and the USA have already detected SARS-CoV-2 in wastewater ( Li et al, 2021a , b ; Malapatty, 2020 ; Medema et al, 2020a , b ). During the early week of the outbreak of COVID-19 in New Haven (Connecticut) several cases were tracked and declared positive by confirming the presence of SARS-CoV-2 RNA in primary sewage sludge from local wastewater treatment plants ( Peccia et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%